System transferability of public hospital facility management between Germany and Iran - Banedj-Schafii, Mandana (Karlsruher Reihe Bauwirtschaft, Immobilien und Facility Management / Institut für Technologie und Management im Baubetrieb, Universität Karlsruhe (TH), 2009)
The subject of this PhD-thesis is the transferability of Facility Management (FM) by using the example of hospitals in Germany and Iran. The intention is to determine the status and significance of facility management in the project countries, to analyse similarities, semblances and differences in order to develop a system transferability model.